Dynamic Environmental Physical Cues Activate Mechanosensitive Responses in the Repair Schwann Cell Phenotype - Michele Fornaro (Cells, 2021)
Schwann cells plastically change in response to nerve injury to become a newly reconfigured repair phenotype. This cell is equipped to sense and interact with the evolving and unusual physical conditions characterizing the injured nerve environment and activate intracellular adaptive reprogramming as a consequence of external stimuli. Summarizing the literature contributions on this matter, this review is aimed at highlighting the importance of the environmental cues of the regenerating nerve as key factors to induce morphological and functional changes in the Schwann cell population. We identified four different microenvironments characterized by physical cues the Schwann cells sense via interposition of the extracellular matrix. We discussed how the physical cues of the microenvironment initiate changes in Schwann cell behavior, from wrapping the axon to becoming a multifunctional denervated repair cell and back to reestablishing contact with regenerated axons.